Endovascular treatment of a vertebral arteriovenous fistula: Case report - (:unkn) unknown (My University, 2009)
In this report, we present a patient with high flow vertebral arteriovenous fistula and its endovascular treatment. The patient was a 25-year-old female with neurofibromatosis type I, presenting with quadriparesis due to the compression of highly dilated epidural venous pouches to cervical spinal cord, and treated with endovascular stent-graft.
Keywords: Arteriovenous; Endovascular; Fistula; Vertebral